1976
DOI: 10.1148/121.3.635
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation Measurements of Whole Blood and Blood Fractions in Computed Tomography

Abstract: Computed tomography (CT) provides an extraordinarily effective means of diagnosing intracranial hemorrhages. Normal blood has a relatively high x-ray attenuation in the circulation and following extravasation, permitting the discrimination by CT of many pathologically enlarged vascular spaces containing circulating blood and/or blood clot (such as arteriovenous malformations and large aneurysms) in addition to recent hemorrhages, from continguous anatomical structures. To promote further understanding of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
116
1
3

Year Published

1978
1978
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(124 citation statements)
references
References 0 publications
4
116
1
3
Order By: Relevance
“…10,9 We measured CT thrombus characteristics on NCCT with the aid of CTA because it was suggested that it is more accurate for low-density thrombi and for patients with high hematocrit levels, which might cause overestimation of the length of the thrombus. 24 DT was determined on multiplanar reformations; this process gives the user a better impression of the 3D anatomy of the vasculature compared with previous measurements on transversal maximum intensity projections. 25 There are several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…10,9 We measured CT thrombus characteristics on NCCT with the aid of CTA because it was suggested that it is more accurate for low-density thrombi and for patients with high hematocrit levels, which might cause overestimation of the length of the thrombus. 24 DT was determined on multiplanar reformations; this process gives the user a better impression of the 3D anatomy of the vasculature compared with previous measurements on transversal maximum intensity projections. 25 There are several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…26 The dynamic expansion of ICH was recognized in the pre-CT era, 27 and subsequently, by using CT, was shown to be maximal in the first few hours following symptom onset. 28 A primary hemorrhagic insult to the brain occurs at ictus with fresh, hypoattenuated liquid blood rapidly clotting to appear hyperattenuated on CT. 29 Larger bleeds have been shown to be more heterogeneous in attenuation at baseline CT. 14 Kim et al 11 found that a low-attenuation "swirl sign" within hematomas on noncontrast CT was associated with increased mortality on univariate but not multivariate analysis. Secondary neural damage is then brought about by edema and blood-breakdown products.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of slice constant thickness and volume, increasing of the blood radio density in proximal aorta (51-55HU) indicates increasing in compactness of the blood. It looks like a throm-bus, which has a higher density of 70-90HU, owing to the exclusion of serum from the clot and consequently increased electron density of the coagulum [10] [11]. High radiodensity near the heart can be associated with the erythrocyte aggregation.…”
Section: Discussionmentioning
confidence: 99%